Allometric equations for orchard and vineyard trees: enhancing AFOLU-based climate change mitigation - Kwak, Myeongja; Lee, Jongkyu; Cheng, Hyocheng; Kim, Iereh; Kim, Juyeong; Woo, Suyoung (Frontiers in Plant Science, 2025)
IntroductionPerennial orchard systems are emerging as important yet underrepresented carbon sinks within the AFOLU sector, which contributes 20–24% of global GHG emissions. Many countries still rely on Tier 1 default values that fail to capture the structural and management characteristics of orchard species. Accurate biomass and carbon estimation, particularly through species-specific allometric equations, is essential for improving Tier 2–3 GHG reporting and recognizing orchards as meaningful contributors to climate-smart land management.MethodsA systematic literature review was conducted using five major databases (2008–2024), following PRISMA guidelines. From 240 initial records, 53 studies met the inclusion criteria. These were categorized into three domains: (i) biometric modeling of fruit-tree biomass, (ii) species-specific allometric equation development, and (iii) carbon-sequestration assessments. Methodological trends, model performance, and research gaps were synthesized to inform an IPCC-aligned framework for orchard-specific emission and removal factors.ResultsMost studies were concentrated in Asia and the Mediterranean and focused on citrus, mango, apple, grape, and olive systems. Power-law allometric models dominated and generally showed high predictive performance (R² > 0.90) with variables such as diameter, height, and crown dimensions. However, major gaps remained: limited data for belowground biomass, juvenile trees, grafted architectures, vineyards, and uncertainty quantification—all of which restrict Tier 2–3 applicability.DiscussionBased on these findings, this review proposes a standardized methodological framework linking biometric measurements, species-specific allometric modeling, remote-sensing integration, and uncertainty analysis to derive orchard-specific emission and removal factors consistent with IPCC guidance. Broader adoption of such protocols would improve transparency and accuracy in national AFOLU inventories and strengthen recognition of perennial orchards as viable nature-based climate solutions that support national net-zero targets.